Aktivitas Antibakteri Kombucha Daun Sirsak (Anonna muricata L.) Terhadap Bakteri Escherichia coli - Rahmasari, Nadia; Rahmawati , Ismi; Saptarini , Opstaria (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Infectious diseases caused by pathogenic bacteria such as Escherichia coli are increasing, especially due to antibiotic resistance. One potential alternative treatment is the use of natural antibacterial compounds, such as those found in soursop leaves (Annona muricata L.). Soursop leaves contain various bioactive compounds, such as flavonoid polyphenols, acetogenins, and tannins, which have antibacterial activity. This study aims to of soursop leaf-based probiotic kombucha fermentation in inhibiting the growth of Escherichia coli. In this study, probiotic kombucha was produced through a fermentation process using Symbiotic Culture of Bacteria and Yeast (SCOBY) with variations in temperature, time, and soursop leaf extract concentration parameters. Activity testing was carried out using the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) methods to assess its antibacterial effectiveness. The results showed that soursop leaf kombucha fermentation had significant antibacterial activity against Escherichia coli. The disc diffusion activity test obtained in this study was 9.1 mm (15% concentration); 5.10 mm (10% concentration); and 2.3 mm (5% concentration) with different concentration variations on the 7th day of fermentation. The resulting inhibition zone diameter for E. coli bacteria indicates that kombucha's antibacterial activity is in the moderate category, as it produced the highest inhibition zone of 9.1 mm. This study demonstrates that soursop leaf kombucha has the potential to be developed as a functional probiotic beverage with effective and natural antibacterial effects.